Laparoscopic two-stage operation for rectal cancer with refractory obstructive colitis after kidney transplantation: a case report - Atsuro Fujinaga; Tomonori Akagi; Tsuyoshi Etoh; Kazuhiro Tada; Yusuke Itai; Yohei Kono; Takahiro Hiratsuka; Kosuke Suzuki; Tomotaka Shibata; Yoshitake Ueda; Manabu Toujigamori; Hidefumi Shiroshita; et al. (Surgical Case Reports)
Abstract Background Although obstructive colitis with colon cancer is not a rare disease, most cases can be improved with conservative therapy. We report a case of a patient who underwent a laparoscopic two-stage operation for rectal cancer with refractory obstructive colitis after kidney transplantation. Case presentation The patient was a 71-year-old man taking immunosuppressants who had previously undergone right living kidney transplantation for chronic nephritis. He presented to hospital complaining of abdominal pain and was diagnosed as having rectal cancer with obstructive colitis. Although conservative therapy by fasting was continued for 5 weeks, his obstructive colitis did not improve. Therefore, we decided to perform a two-stage operation. First, we performed a laparoscopic Hartmann’s operation. It took 6 months for his obstructive colitis to improve after this operation, and then we performed a laparoscopic colorectal anastomosis. There were no postoperative complications in either operation. Conclusion A laparoscopic two-stage operation could be one of the operative options to reduce postoperative complications in patients with comorbidities such as taking immunosuppressants.